Association between the screen time spent watching short videos at bedtime and essential hypertension in young and middle-aged people: a cross-sectional study - Fengde Li; Fangfang Ma; Shangyu Liu; Le Wang; Lishuang Ji; Mingqi Zheng; Gang Liu (BMC Public Health)
Abstract Background Watching short videos is an integral part of the daily lives of young and middle-aged people. Nevertheless, the correlation between the screen time spent watching short videos at bedtime and essential hypertension in young and middle-aged people remains unclear. We aimed to explore the correlation between the screen time spent watching short videos at bedtime and essential hypertension among young and middle-aged people and construct a nomogram prediction model for assessing the probability of developing essential hypertension for these age groups. Methods This study included 4318 young and middle-aged people who underwent medical examinations at Hengshui People’s Hospital between January 2023 and September 2023. The collected data, including self-reported screen time spent watching short videos at bedtime and general information, were partitioned into a training set and a test set, with the former being divided into hypertensive and non-hypertensive groups. R programming language was used for statistical analysis and processing. Results The results of multifactorial logistic analysis showed that screen time of 0< time ≤ 1 h (95% confidence interval [CI]: 2.022–6.082, P<0.05), 2< time ≤ 3 h (95% CI: 1.538–4.665, P<0.05), 3< time ≤ 4 h (95% CI: 5.327–16.691, P<0.05), and time>4 h (95% CI: 21.382–78.15, P<0.05) were independently associated with essential hypertension among young and middle-aged people. Sex, age, screen time, occupation, high-sodium diet, physical activity, sleep, overweight or obesity, diabetes or glucose tolerance abnormality, dyslipidaemia, hyperuricaemia, and family history of hypertension were screened to construct a nomogram prediction model. The model had an area under the curve of the participant’s work characteristics of 0.934 (95% CI: 0.925–0.943), along with a preferably fitted calibration curve. After model validation using the test dataset, the area under the working characteristic curve for participants was 0.911 (95% CI: 0.895–0.928), and it was a well-fitted calibration plot. Conclusions The screen time spent watching short videos at bedtime was significantly associated with essential hypertension in young and middle-aged people, and the nomogram was a good predictor of the risk of essential hypertension among young and middle-aged people.